The utility of dust for forensic intelligence: Exploring collection methods and detection limits for environmental DNA, elemental and mineralogical analyses of dust samples. (March 2023) - Foster, Nicole R.; Martin, Belinda; Hoogewerff, Jurian; Aberle, Michael G.; de Caritat, Patrice; Roffey, Paul; Edwards, Robert; Malik, Arif; Thwaites, Priscilla; Waycott, Michelle; Young, Jennifer
Abstract: Environmental DNA (eDNA), elemental and mineralogical analyses of soil have been shown to be specific to their source material, prompting consideration of using the airborne fraction of soil (dust) for forensic intelligence work. Dust is ubiquitous in the environment and is easily transferred to items belonging to a person of interest, making dust analysis an ideal tool in forensic casework. The advent of Massive Parallel Sequencing technologies means metabarcoding of eDNA can uncover bacterial, fungal, and even plant genetic fingerprints in dust particles. Combining this with elemental and mineralogical compositions offers multiple, complementary lines of evidence for tracing the origin of an unknown dust sample. This is particularly pertinent when recovering dust from a person of interest to ascertain where they may have travelled. Prior to proposing dust as a forensic trace material, however, the optimum sampling protocols and detection limits need to be established to place parameters around its utility in this context. We tested several approaches to collecting dust from different materials and determined the lowest quantity of dust that could be analysed for eDNA, elemental composition and mineralogy, whilst still yielding results capable of distinguishing between sites. We found that fungal eDNA profiles could be obtained from multiple sample types and that tape lifts were the optimum collection method for discriminating between sites. We successfully recovered both fungal and bacterial eDNA profiles down to 3 mg of dust (the lowest tested quantity) and recovered elemental and mineralogical compositions for all tested sample quantities. We show that dust can be reliably recovered from different sample types, using different sampling techniques, and that fungi and bacteria, as well as elemental and mineralogical profiles, can be generated from small sample quantities, highlighting the utility of dust for forensic intelligence. Highlights: The ubiquitous nature of dust makes it a useful tool for forensic intelligence. eDNA, biogeochemistry and sampling method were tested on different dust samples. Both tape lifting and swabbing methods recover discriminatory eDNA dust profiles. Dust eDNA was discriminatory between sites even at very low starting mass. The relative elements and minerals within dust are discriminatory between sites.